2015
DOI: 10.1016/j.amsu.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The surgical admissions proforma: Does it make a difference?

Abstract: Admissions records are essential in communicating key information regarding unwell patients and at handover of care. We designed, implemented and evaluated the impact of a standardised surgical clerking proforma on documentation and clinician acceptability in comparison to freehand clerking. A clerking proforma was implemented for all acute general surgical admissions. Documentation was assessed according to 32 criteria based on the Royal College of Surgeons of England guidelines, for admissions before (n = 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Similar data has been published previously in a number of other hospital specialties. Preprinted pro formas have increased completeness of documentation in paediatric admissions, 5 asthma admissions, 6 stroke admissions, 7 psychiatry admissions 8 and surgical admissions 9 . In addition, pro formas have been shown to improve the diagnosis of patients admitted with a hand injury, 10 and improve compliance with the Best Practice Tariff among hip fracture patients.…”
Section: Nicholas Smallwood Joe Russell Rachel Forbes-pyman and Annmentioning
confidence: 99%
“…Similar data has been published previously in a number of other hospital specialties. Preprinted pro formas have increased completeness of documentation in paediatric admissions, 5 asthma admissions, 6 stroke admissions, 7 psychiatry admissions 8 and surgical admissions 9 . In addition, pro formas have been shown to improve the diagnosis of patients admitted with a hand injury, 10 and improve compliance with the Best Practice Tariff among hip fracture patients.…”
Section: Nicholas Smallwood Joe Russell Rachel Forbes-pyman and Annmentioning
confidence: 99%
“…11, 12 Standardizing entries in clinical notes during the course of care is important for consistency. Structured, agreed upon entries improves documentation.…”
Section: Quality Ofmentioning
confidence: 99%
“…This review showed that the use of a pro forma improves the quality of clerking documentation in elective surgical patients, and that standardisation of the medical record improved the quality of patient care. [6][7][8][9][10][11][12][13][14][15] Evidence is presented across the audits that the use of a pro forma leads to significantly improved documentation for surgical patients, in areas such as previous medical history and medication history. [7,12,13,15] It has also been shown to significantly improve the completion of VTE assessment.…”
Section: Designmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] Evidence is presented across the audits that the use of a pro forma leads to significantly improved documentation for surgical patients, in areas such as previous medical history and medication history. [7,12,13,15] It has also been shown to significantly improve the completion of VTE assessment. [11] The evidence also supports the argument that the use of a pro forma specifically improves documentation of items considered important by the Royal Colleges that are often missed during clerking documentation.…”
Section: Designmentioning
confidence: 99%